2020
DOI: 10.1002/app.50271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulfur in different valence on flame retardance of epoxy resin for light emitting diode

Abstract: A novel phosphorus/nitrogen‐containing flame retardant (DOPO‐AM) was synthesized by 9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) and acrylamide (AM) and its chemical structure was characterized. DOPO‐AM was added into diglycidyl ether of bisphenol‐A (DGEBA) with curing agent m‐xylylenediamine (MXDA)to prepare flame retarded epoxy resin to reduce the possibility of fire. The compounds with different valences sulfur respectively replace partial DGEBA resin to study the effects of sulfur valences on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It was observed that the peak at 2389 cm −1 on DOPO and the peak at 1695 cm −1 on terephthalaldehyde disappeared at APH, and the double band at 3376 cm −1 in 1,5-diaminonaphthalene became a single broad resolution in the APH band [31]. The center was at 3400 cm −1 and the absorption peaks of the P-C and P-O-C bonds were at 760 cm −1 and 1203 cm −1 of APH, respectively, suggesting that aminomethylation occurred during the reaction [32,33]. Figure 1b showed the SEM images of APH.…”
Section: Materials Characterization Of Aphmentioning
confidence: 97%
“…It was observed that the peak at 2389 cm −1 on DOPO and the peak at 1695 cm −1 on terephthalaldehyde disappeared at APH, and the double band at 3376 cm −1 in 1,5-diaminonaphthalene became a single broad resolution in the APH band [31]. The center was at 3400 cm −1 and the absorption peaks of the P-C and P-O-C bonds were at 760 cm −1 and 1203 cm −1 of APH, respectively, suggesting that aminomethylation occurred during the reaction [32,33]. Figure 1b showed the SEM images of APH.…”
Section: Materials Characterization Of Aphmentioning
confidence: 97%
“…[33][34][35] In addition, the high phosphorus content of organophosphates was considered to be a requirement for efficient flame retardants. [36][37][38] However, more and more reports showed that the structure of flame retardants also had an important impact on the flame retardancy of EP. [32,[39][40][41][42] Yoon et al showed that one can enhance the efficiency of flame retardants even with a relatively low phosphorus content by tuning the dynamics and the intermolecular interactions of flame retardants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high phosphorus content of organophosphates was considered to be a requirement for efficient flame retardants. [ 36–38 ] However, more and more reports showed that the structure of flame retardants also had an important impact on the flame retardancy of EP. [ 32,39–42 ] Yoon et al.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy is one of the most important thermosets. It has been widely used in various fields such as coatings, 1 electronic packaging, 2 advanced composites, 3 and so forth. It is outstanding in thermal and mechanical properties, chemical resistance, dimensional stability, and good processability.…”
Section: Introductionmentioning
confidence: 99%